The Artificial Intelligence (AI) framework and the benefits of its use in internal audit - Kontogeorgis, Georgios (International Multilingual Journal of Science and Technology, 2025)
AI is well known today as a valuable tool that can improve our daily lives. In addition, it can improve the efficiency and productivity of many professions, such as the internal auditor. The research methodology is literature review. The primary objectives of the article are twofold: Firstly, to provide a comprehensive description of the institutional framework for the operation of AI internationally, and secondly, to examine the benefits that arise from the use of AI in internal audit units and organisations in general. The significance of the research lies in its examination of artificial intelligence (AI) as a valuable instrument in the arsenal of internal auditors. The findings suggest that AI has the potential to enhance the efficacy of internal audits, reduce the time required for their execution, reduce the frequency of internal audits, and, in general, optimise the operations of companies and organisations.
Keywords: AI; Artificial Intelligence; Corruption; Fraud; Inteligência artificial; Intelligence Artificielle; Internal audit; Management